THE PROBLEMS OF COMMUNICATION IN WORKS OF J. BAUDRILLARD - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The philosophical analysis of problems of communication in works of J. Baudrillard is made.